Biomimetic anti-freezing polymeric hydrogels: keeping soft-wet materials active in cold environments. Issue 2 (7th October 2020) - Jian, Yukun; Handschuh-Wang, Stephan; Zhang, Jiawei; Lu, Wei; Zhou, Xuechang; Chen, Tao
Abstract : The bio-inspired general synthesis strategies of anti-freezing hydrogels and their potential application fields. Abstract : As one of the most outstanding materials, the analysis of the structure and function of hydrogels has been extensively carried out to tailor and adapt them to various fields of application. The high water content, which is beneficial for plenty of applications in the biomedical setting, prevents the adoption of hydrogels in flexible electronics and sensors in real life applications, because hydrogels lose their excellent properties, including conductivity, transparency, flexibility, etc., upon freezing at sub-zero temperatures. Therefore, depressing the liquid–solid phase transition temperature is a powerful means to expand the application scope of hydrogels, and will benefit the chemical engineering and materials science communities. This review summarizes the recent research progress of anti-freezing hydrogels. At first, approaches for the generation of anti-freezing (hydro)gels are introduced and their anti-freezing mechanisms and performances are briefly discussed. These approaches are either based on addition of salts, alcohols (cryoprotectants and organohydrogels), and ionic liquids (ionogels), modification of the polymer network or a combination of several techniques. Then, a concise overview of applications leveraged by the widened temperature resistance is provided and future research areas and developments are envisaged.